The three laws of performance rewriting the future of your organization and your life - Zaffron, Steve (San Francisco Jossey-Bass, 2009)
When something at work isn't going smoothly, managers struggle with what part of the problem to tackle first. Do they start with cost reduction? Or should they go for process improvements first? The authors?who have helped hundreds of companies and individuals change and improve?say spend time and money adjusting the systems in which people operate, rather than targeting people and their performance directly. The authors show that it's in fact possible to change everything at once?with a focus on making such transformations permanent and repeatable.
Includes bibliographical references (p. 209-210) and index.
Keywords: Performance